Características agronômicas, perfil fermentativo e qualidade das silagens do milho BG7046 H colhido em quatro estádios - Joao Pedro Costa Alves de Oliveira (2016)
This study evaluated the corn hybrid BG7046 H. The agronomic traits, nutritional value and the silage produced from the whole corn plant and plant fractions (culm, leaf and ear) were evaluated in four cutting ages (92, 99, 103, 107 days after planting). The corn hybrid BG7046 H was grown in Sete Lagoas, Minas Gerais, in an irrigated field and harvested at the end of the raining season. Agronomic traits data was collected on the cutting days when plant fractions were also separated and the experimental silos were made. The silos were opened on seven different days (1, 3, 5, 7, 14, 28, 56 days after ensiling) for each plant cutting age. The chemical composition of the whole plant, plant fractions and silage were determined. Silage ammoniac nitrogen, pH, effluent loss, gas loss and total loss were obtained in every silo-opening-day for all cutting ages. For agronomical traits: corn ear fraction percentage increased in whole plant as cutting age progressed while the fresh matter yield showed a quadratic effect. Chemical composition differences observed in the plant fractions explained whole plant chemical alterations as age progressed. All parameters, except for EE, were affected by plant cutting age in the silages. For the whole plant, the age effect was observed for DM, ADF, EE, ashes, cellulose and IVDMD. The corn silage presented great silage quality traits and with minimal DM loss in all plant ages. The corn BG7046H should be harvested between 92 and 107 days after planting for silage production without any quality and yield losses.